2006
DOI: 10.1142/s108494670600026x
|View full text |Cite
|
Sign up to set email alerts
|

Normative, Social and Cognitive Predictors of Entrepreneurial Interest in China, Vietnam and the Philippines

Abstract: This study addresses normative, social and cognitive factors related to the interest in becoming an entrepreneur in China, Vietnam, and the Philippines. The study's findings are based on surveys of 782 business students in these countries. A rather consistent pattern of country differences was found on most of the measures, which may reflect differences in the historical, cultural, economic and political contexts of these nations. The results of this study emphasize the importance of developing both self-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 32 publications
4
64
0
8
Order By: Relevance
“…This is quite consistent with the study of Swierczek and Ha (2003) that cultural elements have a strong impact on Vietnamese business innovation and business activities. This argument is further supported by a number of studies showing that potential for entrepreneurial activities and business success can be enhanced by cultural factors in general and organizational culture in particular (Baughn, Cao, Le, Lim, and Neupert, 2006;Deshpande, Farley, and Bowman, 2004).…”
Section: Organizational Culturementioning
confidence: 84%
“…This is quite consistent with the study of Swierczek and Ha (2003) that cultural elements have a strong impact on Vietnamese business innovation and business activities. This argument is further supported by a number of studies showing that potential for entrepreneurial activities and business success can be enhanced by cultural factors in general and organizational culture in particular (Baughn, Cao, Le, Lim, and Neupert, 2006;Deshpande, Farley, and Bowman, 2004).…”
Section: Organizational Culturementioning
confidence: 84%
“…There is an emphasis on developing and using the combined knowledge along with information (knowledge and information) that is used strategically to generate and increase the level of socio-economic growth and development. According to Baughn, Cao, Le, Lim, and Neupert (2006), although there are previous studies on the influence of motivation as the driving force of a participation in entrepreneurship, studies on the technical and business knowledge required for entrepreneurship were inadequate. Liñán et al (2011) studied the factors that influence the level of entrepreneurial intention, and they reported that a high level of knowledge about entrepreneurship can contribute to a more realistic perception of entrepreneurial activity and will affect one's entrepreneurial intentions.…”
Section: Entrepreneurship Knowledgementioning
confidence: 99%
“…Such a culture is found to promote continuous knowledge sharing in order to undertake risky attempts (Niaz Azari and Amooei 2008). Further support was provided by Deshpande et al (2004) and Baughn et al (2006), who all found that the cultural factor, which includes organizational culture, enhances the entrepreneurial orientation leading towards business success in the organization. In addition to this, Nguyen et al (2007) explained that the absence of a strong entrepreneurial culture indicates the presence of a risk avoidance attitude, since culture may positively or negatively affect the willingness to take risks and hence to make business decisions.…”
Section: Discussionmentioning
confidence: 99%